2021
DOI: 10.1002/cti2.1327
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against type I interferon: detection and association with severe clinical outcome in COVID‐19 patients

Abstract: Objectives Impairment of type I interferon (IFN‐I) immunity has been reported in critically ill COVID‐19 patients. This defect can be explained in a subset of patients by the presence of circulating autoantibodies (auto‐Abs) against IFN‐I. We set out to improve the detection and the quantification of IFN‐I auto‐Abs in a cohort of critically ill COVID‐19 patients, in order to better evaluate the prevalence of these Abs as the pandemic progresses, and how they correlate with the clinical course of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
77
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 10 publications
17
77
0
1
Order By: Relevance
“…In our study, 6 patients had high titer of anti IFN- auto-Abs in ELISA and presented all a neutralizing activity in vitro against IFN-. Goncalves et al [9] showed similar results and determined a cut-off of 1000 ng/ml correlated with neutralization assays. In their study, ability of auto-Abs to neutralize only high concentrations of IFN- (10 ng/ml) was investigated.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In our study, 6 patients had high titer of anti IFN- auto-Abs in ELISA and presented all a neutralizing activity in vitro against IFN-. Goncalves et al [9] showed similar results and determined a cut-off of 1000 ng/ml correlated with neutralization assays. In their study, ability of auto-Abs to neutralize only high concentrations of IFN- (10 ng/ml) was investigated.…”
Section: Discussionsupporting
confidence: 81%
“…The full engagement status was significantly less frequent in patient with auto-Abs than in patients without auto-Abs. but like other studies [7,9], there was no difference for comorbidities. Unlike study of Troya et al [7], where a significant correlation between presence of auto-Abs neutralizing type I IFNs, raised levels of C-Protein Reactive and low lymphocytes counts was observed, in our study, no difference was seen for these biological characteristics.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations